Аналіз залежності сталих інтегрування у рівняннях, що описують процеси у RLC-колах при симетричному керуванні перемиканнями ємності та різними співвідношеннями між періодами власних коливань системи і джерела живлення - Шидловська, Н.А. (Технічна електродинаміка, 2012)
Dependences of constants of integration on a parity between the periods of supply voltage of an operating signal and the period of own fluctuations of system are investigated at symmetric control of capacity switchings in a series RLCcircuit of sinusoidal voltage. Cases when the period of an operating signal twice more, is equal and twice less period of input voltage are considered. The analysis used methods of the theory of the differential equations with pulse action. Parities for the integration constants, the including factors depending on parameters of a circuit are received, changing which is possible in certain borders to choose quantity of the switchings necessary for achievement of the steady-state mode.